The effect of return on assets, return on equity, and firm size on company value in infrastructure companies listed on the BEI in 2018-2022 - Budiantara, Jaka Perbawa; Supiyadi, Dedi; Sumawidjaja, Riyandi Nur; Sudaryo, Yoyo (Institute of Computer Science (IOCS), 2024)
In the ongoing industrialization era, business progress is growing rapidly, driven by very tight competition. The decline in share value in the infrastructure sector is the result of intense and growing business competition. This phenomenon encourages investors to make careful considerations before making investment decisions. Thus, the company has the opportunity to strengthen and increase its capital liquidity. This research was conducted on four large companies that have been specified, namely PT Smartfren Telecom Tbk, PT Indosat Tbk, PT Telkom Indonesia (Persero) Tbk, and PT Wijaya Karya (Persero) Tbk. The research method uses a quantitative approach with a purposive sampling method on company financial reports and applies Panel Data Regression techniques. Data analysis using the t test (Partial Test) and Simultaneous Test (F Test) revealed that, partially, Return on Assets (ROA) has no significant effect on company value. On the other hand, Return on Equity (ROE) and Company Size (Firm Size) have a significant effect on company value. Simultaneously, ROA, ROE, and Firm Size together influence company value by 48%, while other factors also play a role. The analysis was carried out through multiple linear regression using Eviews 10 software and described the calculation results of the classical assumption deviation test. This research is expected to provide considerations for companies in increasing company value and attracting the interest of more investors.